(untitled) (Cadernos de Sociomuseologia, 2016)
This article aims to present a brief historical and conceptual trajectory on the field of social museology and Sociomuseology. The discussion seeks to identify how the discussions and debates in this area affected in the way how museums work, with the creation of community museums and the reframing of the narrative and museological practices of existing museums. As well, it aims to identify how it also affected in the theoretical reflections in the field of museology. It still intends to discuss the connections and differences between what is social museology and Sociomuseology, as so the dilemmas and conflicts in this academic field. Keywords: social museology, Sociomuseology, community museums